Primary Cutaneous Atypical Spindle Cell Lipomatous Tumor. (8th November 2021) - Tchack, Madeline S.; Broscius, Michael; Reichel, Martin
Abstract : This report documents an exophytic, pedunculated nodule in a 74-year-old man that upon histopathological examination revealed an atypical spindle cell/pleomorphic lipomatous tumor (ASPLT) confined to the papillary and reticular dermis, representing the fourth documented case within the skin. Despite the overt pleomorphic changes present histologically, the patient is free of metastasis or recurrence five years after surgery.